Development and Assessment of a Prototype for a Training Program to Enhance Implementation Leadership of Unit Nurse Managers in the Chinese Nursing Context - Chen, Wenjun (Université d'Ottawa / University of Ottawa, 2023)
Background: Unit nurse managers are in a key position to influence the implementation of evidence-based practice (EBP) in nursing. However, research indicates that nurse managers in China lack the competencies and behaviours to effectively lead implementation. The purpose of this study was to develop a prototype for an implementation leadership training program for unit nurse managers in China, and assess the prospective acceptability of the prototype. Methods: The dissertation was conducted in three study phases using multiple methods: 1) a mixed-methods systematic review of leadership development interventions for managers supervise nurses; 2) a qualitative descriptive study using an integrated knowledge translation (IKT) approach to develop a prototype for an implementation leadership training program based on the Ottawa Model of Implementation Leadership in Changsha, China; and 3) a qualitative descriptive study to investigate the prospective acceptability of the prototype among potential program deliverers and participants (n=14) from three tertiary hospitals in Changsha, China. Results: The systematic review analyzed 69 studies and found that leadership development interventions, including lectures, group work, and mentoring, positively impacted managers' leadership competencies in supporting, developing, and recognizing nurses. However, obstacles such as understaffing, time constraints, and lack of support hindered the application of these competencies in practice. In the co-development stage, nurse managers (n=7) identified all 14 O-MILe behaviours as important for EBP implementation, with some behaviours requiring modifications for clarity and cultural relevance. Managers outlined specific actions related to clinical practices, EBP, nurses, patients, interprofessional staff, incentives, resources, organization, and external entities. They emphasized the need for competencies in EBP, professional nursing, and implementation leadership. The training program prototype consisted of five interactive modules to be delivered through multimodal forms such as lectures, group discussions and coaching. Unit nurse managers (n=14) found the prototype acceptable, expecting it to enhance care provision and align with their professional values. Time constraints, the COVID-19 impact, and support from senior leadership were identified as influencing future participation. Conclusion: The prototype for the implementation leadership training program was perceived as acceptable to unit level nursing managers in the hospital context in Changsha, China. Future research is needed to explore the impact of the training program on enhancing implementation leadership competencies and behaviours of unit nurse managers, and the subsequent influence on nursing practice and patient outcomes.
Keywords: Unit nurse managers; Implementation leadership; Training program prototype; Chinese nursing context